Early Relapse After Autologous Stem Cell Transplantation in Multiple Myeloma is Still Prognostic in The Era of Novel Agents - Semih Başcı; Tuğçe Nur Yiğenoğlu; Bahar Uncu Ulu; Mehmet Bakırtaş; Derya Şahin; Tahir Darçın; Jale Yıldız; Alparslan Merdin; Nuran Ahu Baysal; Dicle İskender; Merih Kızıl Çakar; Mehmet Sinan Dal; Tuba Hacıbekiroğlu; Fevzi Altuntaş (Medical Laboratory Technology Journal, 2020)
Significant improvements in the prognosis of Multiple Myeloma(MM) have recently observed in the era of novel agents. Induction treatment, including new agents followed by conditioning regimen and upfront autologous stem cell transplantation(ASCT), has been accepted as the standard treatment approach for newly diagnosed eligible MM patients. Despite novel agents, upfront ASCT is still superior to conventional chemotherapy alone. Previous studies revealed that the duration between ASCT and relapse had predicted overall survival(OS), and meantime, it was widely used to determine the potential benefit from a second ASCT. However, the majority of the data collected reflects the treatment modalities before novel agents. In this study, we aimed to investigate the impact of post-transplantation early relapse(ER) on survival in the era of novel agents. The results of 155 MM patients that underwent ASCT at our center between January 2010 and May 2018 were analyzed retrospectively. The median follow-up duration was 20 months in the ER group, 27 months in the non-ER group, and 24 months in all patients. 33.3% of patients in the ER group and 71.4% of patients in the non-ER group were alive at the time of analysis. Median OS was 20.77±3.66 months in the ER group and 40.89±4.21 months in the non-ER group. We found a statistically significant relationship between the ER and the poor OS (p: